Trematodes of the Hoplerythrinus unitaeniatus (Erythrinidae) «shuyo» and Pterodoras granulosus (Doradidae) «cahuara» in Yurimaguas, Loreto, Peru - Delgado E., Abraham (2017)
Five specimens of Hoplerythrinus unitaeniatus «shuyo» (Erythrinidae) and one of Pterodoras. granulosus «cahuara» (Doradidae) were assessed in Yurimaguas district, Alto Amazonas, Loreto, Peru in February 20014. A larva of the trematode Ithyoclinostomum dimorphum and 13 larvae of Sphincterodiplostomum musculosum in H. unitaeniatus in the visceral surface, and 18 adult of Dadaytrema oxycephala from the small bowel of P. granulosus were found. This is the first report of metacercariae of I. dimorphum and S. musculosum in Peru. H. unitaeniatus is a new host for S. musculosum. D. oxycephala in P. granulosus is reported in Peru.